2023
DOI: 10.3389/fcvm.2023.1141083
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of a novel pathogenic variant in the gene LMNA associated with cardiac laminopathies found in Ecuadorian siblings: A case report

Abstract: IntroductionCardiac laminopathies are caused by mutations in the LMNA gene and include a wide range of clinical manifestations involving electrical and mechanical changes in cardiomyocytes. In Ecuador, cardiovascular diseases were the primary cause of death in 2019, accounting for 26.5% of total deaths. Cardiac laminopathy-associated mutations involve genes coding for structural proteins with functions related to heart development and physiology.Family descriptionTwo Ecuadorian siblings, self-identified as mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…However, we could not evaluate the genomic data of the proband's family, therefore we are not able to determine if this pathogenic variant is inherited. In Ecuador, few studies have reported ancestry analyses and cardiovascular diseases (Cadena-Ullauri et al, 2022;Guevara-Ramírez et al, 2023). In the present case report, the proband shows a high European proportion (40.3%) in ancestry proportion analysis.…”
Section: Diagnostic Assessmentsupporting
confidence: 42%
See 1 more Smart Citation
“…However, we could not evaluate the genomic data of the proband's family, therefore we are not able to determine if this pathogenic variant is inherited. In Ecuador, few studies have reported ancestry analyses and cardiovascular diseases (Cadena-Ullauri et al, 2022;Guevara-Ramírez et al, 2023). In the present case report, the proband shows a high European proportion (40.3%) in ancestry proportion analysis.…”
Section: Diagnostic Assessmentsupporting
confidence: 42%
“…In Ecuador, few studies have reported ancestry analyses and cardiovascular diseases ( Cadena-Ullauri et al, 2022 ; Guevara-Ramírez et al, 2023 ). In the present case report, the proband shows a high European proportion (40.3%) in ancestry proportion analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by identifying mutations associated with CVDs, NGS facilitates early diagnosis, personalized pharmacological approaches, and identification of novel biomarkers. Thus, NGS is a valuable tool in CVD management [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, such studies are limited in Ecuador, a low- and middle-income country. Only a few studies have been conducted, yielding interesting results related to the Ecuadorian population [ 7 - 9 ]. Several challenges contribute to this gap, encompassing economic, infrastructural, and educational obstacles.…”
Section: Introductionmentioning
confidence: 99%